2021
DOI: 10.3389/fpsyt.2021.693103
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Change in the Course of a Pilot Study of a Step-Down Treatment Approach of Inpatient and Anorexia Nervosa-Specific Home Treatment and Its Effects on Treatment Outcome

Abstract: Introduction: Anorexia nervosa (AN) is a serious mental disorder that typically manifests in adolescence. Motivation to change is an important predictor for treatment outcome in adolescent AN, even though its development over the often long therapeutic process, with transitions between treatment settings, has not yet been studied. In this pilot study, the course of motivation to change and its effect on treatment outcome were investigated over the course of a step-down treatment approach during a 12-month obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
0
0
1
Order By: Relevance
“…A recently published pilot study on this approach including 22 patients with severe AN who were admitted for IP demonstrated that this stepped-care approach was feasible and safe for adolescent patients with AN and thus considered as a promising new approach to reducing the duration of hospitalization for IP and, furthermore, to potentially improving the longer-term outcomes for this patient population [71]. It was found that all patients completing the home treatment program not only showed a significant improvement in their ED behavior and general psychopathology but, moreover, achieved significant weight gain, which was maintained one year after hospital admission [71,83]. Furthermore, all patients reported high treatment satisfaction, and their motivation to change increased significantly during the treatment and remained stable at the 1-year follow-up [71,83].…”
Section: Home Treatment For Child and Adolescent Anmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published pilot study on this approach including 22 patients with severe AN who were admitted for IP demonstrated that this stepped-care approach was feasible and safe for adolescent patients with AN and thus considered as a promising new approach to reducing the duration of hospitalization for IP and, furthermore, to potentially improving the longer-term outcomes for this patient population [71]. It was found that all patients completing the home treatment program not only showed a significant improvement in their ED behavior and general psychopathology but, moreover, achieved significant weight gain, which was maintained one year after hospital admission [71,83]. Furthermore, all patients reported high treatment satisfaction, and their motivation to change increased significantly during the treatment and remained stable at the 1-year follow-up [71,83].…”
Section: Home Treatment For Child and Adolescent Anmentioning
confidence: 99%
“…It was found that all patients completing the home treatment program not only showed a significant improvement in their ED behavior and general psychopathology but, moreover, achieved significant weight gain, which was maintained one year after hospital admission [71,83]. Furthermore, all patients reported high treatment satisfaction, and their motivation to change increased significantly during the treatment and remained stable at the 1-year follow-up [71,83]. Additionally, the ability of caregivers to handle their children's ED significantly improved throughout treatment, while their perceived burden and depressive symptoms decreased [71,84].…”
Section: Home Treatment For Child and Adolescent Anmentioning
confidence: 99%
“…Bei den Patientinnen fand sich zusätzlich ein deutlicher Anstieg der Lebensqualität. Interessanterweise nahm die Motivation der Patientinnen, ihre Erkrankung zu überwinden, in dem Zeitraum zwischen dem Ende vom Home-Treatment und dem Katamnesedatum nach einem Jahr weiter zu [36].…”
Section: Ergebnisse Der Pilotstudieunclassified